HD-Sign: Hardware Based Digital Signature Generation Using True Random Number Generator - G, Anahita; KPM, Krishnapriya; Prasad R, Shiva; Kumar N, Mohan (International Journal of Engineering and Technology, 2018)
With the recent advancements in the field of computing, a fair share of easier and safer practices to exchange and share information between multiple parties have propped up. While some of these are improvisations, a few such as the Digital Signatures, have fast replaced conventional signing practices. It’s wide use and acceptance in the industry as well as officially, has necessitated higher security to protect data integrity and privacy. These digital Signatures are generated on the basis of various schemes that are designed to accommodate efficiency, crypto security and algorithmic complexity. This paper proposes an alternate method named HD-SIGN for generating these digital signatures in accordance with Secure Hash Function and 512-bit SRNN cryptographic algorithm. With the aid of a TRNG module, a modification to produce a large number with two prime factors and a set of natural numbers in a pair of public and private keys has been incorporated. The LSFR based TRNG module which helps maintain the ‘True Randomness’ of any generated number has been used for this purpose. Further, the random nature of the generated sequence to be used in the digital signature, has been tested with the help of standard NIST tests. The Hamming distance has also been analyzed as a security metric for the proposal, implying the degree of unpredictability of the generated true random sequences.